DAMPAK LITERASI DIGITAL TERHADAP KREATIVITAS MAHASISWA - Niken Ananda; Rifda Afifah; Eka Sastrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Student creativity is developed through existing digital media. The aim of thisresearch is to understand the impact of digital literacy on student creativity, so thatstudents can apply it and become creative and innovative individuals. This researchuses a survey method given to students who carry out various activities using digitalliteracy. Among them are Jambi University PGSD students. In the process ofcollecting data, researchers used questionnaires and documentation.Questionnaires are used by researchers as a tool to collect data which is distributedto respondents via Google Form (online). Meanwhile, documentation is thecollection of evidence during the research process which includes reports on theresults of distributing questionnaires, photos, correspondence, and so on. Thepopulation in this study were 82 Semester PGSD UNJA students three the samplefrom the population in this study was 45 people taken using the Slovin formula. Theresults of the research show that there is an impact of social media on the creativityof PGSD UNJA students seen from the results of the respondents. This shows thatstudents agree that digital literacy based on social media has an impact on thedevelopment of student creativity.